2014
DOI: 10.1111/tri.12499
|View full text |Cite
|
Sign up to set email alerts
|

Delayed trough level measurement with the use of prolonged-release tacrolimus

Abstract: Summary Trough concentrations of prolonged‐release tacrolimus are usually measured at 24 h after taking the drug in the morning. It is impractical to measure these trough concentrations in patients who visit the outpatient clinic in the afternoon. Trough concentrations obtained in the afternoon may also be suitable for estimating the 24‐h exposure. We therefore aimed to assess the usefulness of tacrolimus concentrations measured at 32 h postdose for therapeutic drug monitoring in renal transplant patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…There was not always a strong indication of association (with sometimes only 60 % of variability explained). In one study involving 26 stable renal transplant recipients, tacrolimus trough measurements taken from 26 to 32 h after Advagraf Ò dosing were found to have a correlation with tacrolimus AUC 0-24 similar to that of a measurement taken 24 h after dosing [58]. The authors suggested that in patients in whom it was impractical to get a 24-h trough measurement because of an afternoon outpatient clinic appointment, a later 'delayed' trough value may still be useful, although the trough target range would need to be lowered accordingly.…”
Section: Xrmentioning
confidence: 83%
“…There was not always a strong indication of association (with sometimes only 60 % of variability explained). In one study involving 26 stable renal transplant recipients, tacrolimus trough measurements taken from 26 to 32 h after Advagraf Ò dosing were found to have a correlation with tacrolimus AUC 0-24 similar to that of a measurement taken 24 h after dosing [58]. The authors suggested that in patients in whom it was impractical to get a 24-h trough measurement because of an afternoon outpatient clinic appointment, a later 'delayed' trough value may still be useful, although the trough target range would need to be lowered accordingly.…”
Section: Xrmentioning
confidence: 83%
“…An article by van Boekel et al (2015) assessed the correlation between blood concentrations of ER-Tac taken at C 32 and AUC 0-24 . 22 The study was conducted under the premise that exposure assessed at C 32 would be more convenient to the patient by allowing for afternoon clinic appointments. That study found good correlations between tacrolimus concentrations (drawn 24, 26, 28, 30, and 32 hours postdose) and AUC 0-24 (P < .01 for each point).…”
Section: Discussionmentioning
confidence: 99%
“…That study found good correlations between tacrolimus concentrations (drawn 24, 26, 28, 30, and 32 hours postdose) and AUC 0-24 (P < .01 for each point). 22 The relevance of alternative monitoring strategies is highlighted in a recently published study by Valizadeh et al (2016). 23 They found that among 16 potential stressors following a kidney transplant, patients rated "travelling for check-up" as the fourth highest stressor, right after "fear of graft rejection," "financial pressure," and "uncertainly about future health."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For long‐term follow‐up novel sampling strategies, such as with dried blood spot (DBS) finger pricks (require only one drop of blood applied on filter paper) could be of great value to address the challenges with AUC determination and LSS encountered in children. A tacrolimus DBS assay is currently used for clinical practice in adults in our institute …”
Section: Discussionmentioning
confidence: 99%